2019
DOI: 10.3390/agronomy9100621
|View full text |Cite
|
Sign up to set email alerts
|

Appraising Endophyte–Plant Symbiosis for Improved Growth, Nodulation, Nitrogen Fixation and Abiotic Stress Tolerance: An Experimental Investigation with Chickpea (Cicer arietinum L.)

Abstract: Chickpea is an important leguminous crop that improves soil fertility through atmospheric nitrogen fixation with the help of rhizobia present in nodules. Non-rhizobia endophytes are also capable of inducing nodulation and nitrogen fixation in leguminous crops. The aim of the current study was to isolate, characterize and identify the non-rhizobia endophytic bacterial strains from root nodules of chickpea. For this purpose, more than one hundred isolates were isolated from chickpea root nodules under aseptic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…In the present study, the highest dry biomass and leaf area were noted at pH 7 under Cd toxicity, which supported the earlier finding that neutral to the slightly alkaline environment encountered heavy metal toxicity, especially Cd [ 50 52 ]. Our results showed that Cd uptake and utilization in wheat seedlings were declined with elevated soil pH from 5 to 7, while improved with further increase in pH from 7 to 9, which were in line with previous findings [ 53 55 ]. Cd bioavailability at lower pH (5) was high, which might be due to more release of Cd from adsorption sites, entering the nutrient solution, and consequently, greater mobility and increased availability to wheat plants ( Fig 5 and Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the highest dry biomass and leaf area were noted at pH 7 under Cd toxicity, which supported the earlier finding that neutral to the slightly alkaline environment encountered heavy metal toxicity, especially Cd [ 50 52 ]. Our results showed that Cd uptake and utilization in wheat seedlings were declined with elevated soil pH from 5 to 7, while improved with further increase in pH from 7 to 9, which were in line with previous findings [ 53 55 ]. Cd bioavailability at lower pH (5) was high, which might be due to more release of Cd from adsorption sites, entering the nutrient solution, and consequently, greater mobility and increased availability to wheat plants ( Fig 5 and Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…[24]. They effectively colonize plant roots, thus helping the improvement of plant growth and nutrient acquisition [27,28]. These bacteria can also induce tolerance against different biotic and abiotic stresses in plants through several indirect mechanisms [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…They effectively colonize plant roots, thus helping the improvement of plant growth and nutrient acquisition [27,28]. These bacteria can also induce tolerance against different biotic and abiotic stresses in plants through several indirect mechanisms [27,29]. Moreover, bacterial inoculation improves soil health by fixing atmospheric nitrogen [30,31], production of plant hormones, siderophores and exopolysaccharides [32], and phytoremediation of heavy metals and other organic pollutants [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Increased chlorophyll content due to inoculation might happen as a result of enhanced Mg 2+ that accelerated the production of photosynthates [76]. The increase in chlorophyll content is also correlated to improvement in nutrient uptake by crop plants due to phosphate solubilization, siderophores production and IAA production by inoculated strains [77,78].…”
Section: Discussionmentioning
confidence: 99%